Genexp--a genetic network simulation environment - Vu, Tra Thi; Vohradsky, Jiri (Bioinformatics (Oxford, England), 2002)
UNLABELLED: An environment for simulation of dynamics of genetic regulatory networks is presented. The model is based on the recurrent neural network principle and allows to interactively simulate various genetic regulatory interactions under different features of the system. The results are displayed graphically. AVAILABILITY: http://proteom.biomed.cas.cz/genexp
Keywords: Software; Computer Simulation; software; Genetic Engineering; genomika; geny; genom; Models, Genetic; Genes; Gene Expression Profiling; počítačová simulace; Gene Expression Regulation; genetické inženýrství; Genome; Genomics; modely genetické; regulace genové exprese; stanovení celkové genové exprese